Behavioral Microbiomics: A Multi-Dimensional Approach to Microbial Influence on Behavior - Wong, Adam C.-N.; Holmes, Andrew; Ponton, Fleur; Lihoreau, Mathieu; Wilson, Kenneth; Raubenheimer, David; Simpson, Stephen J. (Frontiers in Microbiology, 2015)
The role of microbes as a part of animal systems has historically been an under-appreciated aspect of animal life histories. Recently, evidence has emerged that microbes have wide-ranging influences on animal behavior. Elucidating the complex relationships between host–microbe interactions and behavior requires an expanded ecological perspective, involving the host, the microbiome and the environment; which, in combination, is termed the holobiont. We begin by seeking insights from the literature on host–parasite interactions, then expand to consider networks of interactions between members of the microbial community. A central aspect of the environment is host nutrition. We describe how interactions between the nutrient environment, the metabolic and behavioral responses of the host and the microbiome can be studied using an integrative framework called nutritional geometry, which integrates and maps multiple aspects of the host and microbial response in multidimensional nutrient intake spaces.